Exploring the genetic variability of citrus butterfly (Papilio demoleus) using DNA barcode - JINDAL, VIKAS (The Indian Journal of Agricultural Sciences, 2020)
The present study is first and initial report from India on developing barcodes and molecular identification of citrus swallow tail butterfly (Papilio demoleus L.) based on mtCOI region and species composition from Abohar, Jalandhar, Ludhiana, Sangrur areas of Punjab on citrus host plants. The corresponding genomic DNA isolation, PCR amplification, detectable genetic divergence, molecular identification and phylogenetic tree were assessed. Using the specific set of primers the samples yielded specific fragment of 658 bp. The amplified PCR product was sequenced and identified as Papilio demoleus and submitted to BOLD database. The 658 bp mtCOI gene sequences from Abohar, Ludhiana, Jalandhar were 100% similar however the sequence from Sangrur region show mutations at three different positions showing a variation of 0.45% from rest of the populations of Punjab. The phylogenetic tree was developed and it was revealed that all the populations of Punjab are in same cluster and when compared with populations from other countries, it form two main clusters which are different from each other by 3.70%. The cluster one includes all the populations of Australia, India, USA and Pakistan and the cluster two include totally different populations from Canada. In cluster one the populations from Australia and USA forms one subgroup while populations from India and Pakistan form second subgroup.